2010
DOI: 10.1530/eje-10-0420
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor expression in endocrine tumors is associated with high stromal expression of α-smooth muscle actin

Abstract: Objective: Complications due to fibrosis development are common in patients with well-differentiated endocrine carcinomas in the small intestine (ileal carcinoids). Connective tissue growth factor (CTGF) expression in ileal carcinoids may be related to this fibrosis development. This study aimed to examine CTGF expression in relation to local myofibroblast differentiation in a large series of ileal carcinoids and in different types of endocrine tumors. Methods: Immunoreactivity (IR) for CTGF and a-smooth muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Serotonin production is occasionally seen in GNETs (Tsolakis et al 2008) and its relationship to CTGF is not known in these tumours. In a recent study, a correlation was observed between CTGF and serotonin production in NETs even when ileal NETs were excluded from the analysis (Cunningham et al 2010). IGF1 expression has been reported only in ileal NETs but occasional cases were investigated (Nilsson et al 1992, Wulbrand et al 2000.…”
Section: Introductionmentioning
confidence: 97%
“…Serotonin production is occasionally seen in GNETs (Tsolakis et al 2008) and its relationship to CTGF is not known in these tumours. In a recent study, a correlation was observed between CTGF and serotonin production in NETs even when ileal NETs were excluded from the analysis (Cunningham et al 2010). IGF1 expression has been reported only in ileal NETs but occasional cases were investigated (Nilsson et al 1992, Wulbrand et al 2000.…”
Section: Introductionmentioning
confidence: 97%
“…Although high expression of CCN2 is the hallmark of good prognosis of CRC, its roles in CRC cell differentiation and proliferation are still under investigation. In previous studies, Cunningham et al [38] showed that CCN2 expression was positively correlated with α-smooth muscle actin expression, which in turn indicated a potential role for CCN2 in myofibroblast-mediated fibrosis associated with ileal carcinoids. Moreover, Kaltsas et al [39] in 2010 demonstrated that CCN2 involved in the neoplastic transformation into ileal carcinoids is positively correlated with tumours larger than 1 cm.…”
Section: Correlation Of Ccn Protein With Advanced Crc Progressionmentioning
confidence: 94%
“…Treatment with CTGF-neutralizing antibodies has already been shown to decrease tumour growth and metastasis in pancreatic cancer models (Leask & Abraham 2006). SI-NETs have a high expression of CTGF compared to other neuroendocrine tumours (Kidd et al 2007c, Cunningham et al 2010. Immunoreactivity was strongest in SI-NET cells adjacent to fibrovascular stroma, suggesting a local effect on the tumour stroma interaction at the invasion border.…”
Section: Connective Tissue Growth Factor (Ctgf Also Known As Ccn2)mentioning
confidence: 99%
“…In contrast to quiescent fibroblasts, CAFs are able to proliferate, produce growth factors and ECM (Kalluri 2016). Compared to other neuroendocrine tumours, SI-NETs have a high expression of αSMA in the fibroblast component of the TME both in primary tumours and metastases (Facco et al 1998, Kidd et al 2007c, Cunningham et al 2010. Further evidence on the presence of synthetic fibroblasts in SI-NETs was detected in primary cultures in which cells from the tumour stroma developed the typical stellate shape of CAFs and increased growth factor transcription after stimulation with transforming growth factor beta 1 (TGFβ1, see later) (Kidd et al 2007c).…”
Section: Tumour Microenvironment (Tme)mentioning
confidence: 99%
See 1 more Smart Citation